2010
DOI: 10.1007/s11368-010-0321-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of waste water treatment on river metal concentrations: removal or enrichment?

Abstract: Purpose Discharge of untreated domestic and industrial waste in many European rivers resulted in low oxygen concentrations and contamination with trace metals, often concentrated in sediments. Under these anoxic conditions, the formation of insoluble metal sulfides is known to reduce metal availability. Nowadays, implementation of waste water treatment plants results in increasing surface water oxygen concentrations. Under these conditions, sediments can be turned from a trace metal sink into a trace metal sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…This could be caused by exposure to oxygen, either by dredging operations or by drying effects (condition caused by a decrease in the water level). It could impact directly on the environment because of the sediment acidification and the heavy metal release into the water column while their bioavailability seems to be incremented (Förstner 2004;Seidel et al 2006a, b;Cappuyns et al 2006;Di Nanno et al 2007;Teuchies et al 2011;Porzionato et al 2014).…”
Section: Responsible Editor: Robert Duranmentioning
confidence: 99%
“…This could be caused by exposure to oxygen, either by dredging operations or by drying effects (condition caused by a decrease in the water level). It could impact directly on the environment because of the sediment acidification and the heavy metal release into the water column while their bioavailability seems to be incremented (Förstner 2004;Seidel et al 2006a, b;Cappuyns et al 2006;Di Nanno et al 2007;Teuchies et al 2011;Porzionato et al 2014).…”
Section: Responsible Editor: Robert Duranmentioning
confidence: 99%
“…Nowadays, surface water quality has improved due to enhanced sewage treatment, source control and other measures and it is expected that sediments will now act as a source of contamination for macroinvertebrates and organisms of higher trophic levels (Salomons and Brils 2004;Teuchies et al 2011). Consequently, achieving a "good ecological status" of surface waters, as required by the European Water Framework Directive (WFD, 2000/60/EC), may strongly depend on the management of sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies in marine/estuarine systems have observed metal release, but the overall impact on water column dissolved copper concentrations was minor. Teuchies et al () observed a release of dissolved copper after aeration in laboratory systems, but the effect was not observable in the field. There has been evidence presented that once copper precipitates with sulfide in sediment, it is not readily released after exposure to oxic conditions (Simpson et al ; Sundelin and Eriksson ; De Jonge et al ; Costello et al ).…”
Section: Synthesis Of Field and Model Datamentioning
confidence: 99%